Identifikasi Kearifan Lokal Kampung Bulakan sebagai Upaya Pelestarian Lingkungan Cagar Alam Gunung Tukung Gede - Muhamad Wahyudin; Ratu Nadilah; Najla Auliatu Sholihah; Nahli Hanif Digravida; Muhamad Nazibullah; Dava Machmud Qivlan; Ryan Dwi Juniardi (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Local culture plays an important role in maintaining ecosystem balance and environmental sustainability. This research aims to identify the local culture of the people of Kampung Bulakan that contribute to the preservation of the Gunung Tukung Gede Nature Reserve. The research method uses a qualitative approach through the ethnographic method, which is by studying human behavior, such as the customs and habits of the community in a certain place. This method is carried out through in-depth interviews with community leaders and local residents, as well as observations of the surrounding environment to gain an understanding from the perspective of the local community. The results of the study showed four main forms of local culture, namely the existence of the Tiger Monument, the prohibition of breaking tree branches with hands, the prohibition of activities outside the house after 22.00, and the tradition of stirring. This practice functions to prevent vegetation damage, preserve 167 types of flora with an average density of 310 trees per hectare, and maintain the habitat of the Javan leopard (Panthera pardus melas). In conclusion, the local culture of Kampung Bulakan is an effective and relevant community-based conservation strategy to continue to be preserved.